Comment on ``Continuous groups of transformations and time-dependent invariants’’ - Torres del Castillo, G.F. (Revista Mexicana de Física E, 2008)
Some errors in a recent paper ( Rev. Mex. Fís. E 53 (2007) 112) dealing with the Noether theorem are pointed out.